2008
DOI: 10.1016/j.marchem.2007.12.002
|View full text |Cite
|
Sign up to set email alerts
|

New perspectives on radium behavior within a subterranean estuary

Abstract: Abstract:Over the past decade, radium isotopes have been frequently applied as tracers of submarine groundwater discharge (SGD). The unique radium signature of SGD is acquired within the subterranean estuary, a mixing zone between fresh groundwater and seawater in coastal aquifers, yet little is known about what controls Ra cycling in this system. The focus of this study was to examine controls on sediment and groundwater radium activities within permeable aquifer sands (Waquoit Bay, MA, USA) through a combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
105
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(125 citation statements)
references
References 45 publications
9
105
3
Order By: Relevance
“…2C). Gonneea et al (2007) found that in the STZ Ra is sorbed onto Fe and Mn (hydr)oxides precipitating at the interface between the buffered saline water (high pH, low pε and high dissolved Mn and Fe concentrations) and fresh shallow groundwater (relatively low pH and high pε). Although Ra has higher affinity for Mn (hydr)oxides (Moore and Reid, 1973), Fe (hydr)oxides occur in one order of magnitude higher concentrations and may have just as much influence on the aquifer Ra distribution.…”
Section: Sources Of This Labile 226mentioning
confidence: 99%
See 3 more Smart Citations
“…2C). Gonneea et al (2007) found that in the STZ Ra is sorbed onto Fe and Mn (hydr)oxides precipitating at the interface between the buffered saline water (high pH, low pε and high dissolved Mn and Fe concentrations) and fresh shallow groundwater (relatively low pH and high pε). Although Ra has higher affinity for Mn (hydr)oxides (Moore and Reid, 1973), Fe (hydr)oxides occur in one order of magnitude higher concentrations and may have just as much influence on the aquifer Ra distribution.…”
Section: Sources Of This Labile 226mentioning
confidence: 99%
“…In the absence of Fe and Mn (hydr)oxides in sediments, Ra can quickly desorb as the salinity of the pore water increases (Li et al, 1976;Elsinger and Moore, 1980). When radium is bound to Fe and Mn (hydr)oxides, the potential release under reducing conditions is much greater than desorption driven only by increases in ionic strength (Gonneea et al, 2007).…”
Section: Sources Of This Labile 226mentioning
confidence: 99%
See 2 more Smart Citations
“…The uncertainty associated with the groundwater end-member AR may also be reduced by collecting multiple (n 3) samples of the groundwater end-member and calculating the AR as the slope of the linear regression between short-and long-lived Ra isotope activities (Garcia-Solsona et al 2010b). However, we note that in some situations Ra isotope activities in groundwater are highly variable on a small spatial scale (e.g., Swearman et al 2006;Gonneea et al 2008) due to the multiple processes that affect groundwater chemistry in the subterranean estuary, making it difficult or impossible to identify which groundwater should be considered the discharging end-member or to define what the characteristics of this end-member are.…”
Section: Using Ar To Estimate Water Mass Ages (Moore 2000a and Moore mentioning
confidence: 93%